How to mobilise users' experiential knowledge in the evaluation of advanced technologies and practices in Quebec? The example of the permanent users' and relatives' panel - Marie‐Pascale Pomey; Sandra Pelaez; Enora Le Roux; Oliver Demers‐Payette; Marie‐Claude Sirois; Louis Lochhead; Isabelle Ganache; Louise Normandin; Audrey L'Espérance; Michèle deGuise (Health Expectations)
Abstract Introduction With the purpose of supporting scientific professionals and helping them to better integrate the expertise of users in their work, a users' and relatives' panel (URP) was set up at the National Institute for Excellence in Health and Social Services in Quebec (INESSS), Canada for the social services and mental health directorate. URPs are advisory structures that mobilise the experiential knowledge of people affected by various issues. Objectives The objective of this study is to assess from a diverse stakeholders' perceptions: (1) the experience of developing and implementing the URP within the context of an Agencies for Health Technology Assessment and Assessment of Social Services (AHTAASS), (2) the contribution of such a URP, (3) the challenges encountered and (4) the perspectives of improvement for the following years. Methodology We conducted a qualitative descriptive evaluation study. Nineteen interviews were conducted: six with URP members and 13 with staff representatives. The documents related to the creation of the panel, the URP minutes summarising the discussions and the reports published during that period were collected and analysed. Following a preliminary round of data analysis, a debriefing meeting was conducted with a few participants to validate the results. Results The panel was set up as part of the INESSS' desire to better integrate experiential knowledge into its recommendations. Twelve projects were presented to the panel on various themes. The URP enabled health professionals to consider dimensions they had not identified, to better integrate the experiential data collected from users into their work and to develop recommendations that made more sense to users. Panel members and INESSS professionals learned to work together, moving the working methods from consultation to collaboration and even coconstruction. Based on the panel's significant contribution, the INESSS decided to maintain it and to strengthen its place in its system to better integrate the experiential knowledge of users into its work. Conclusion This research illustrates how AHTAASS can set up a URP composed exclusively of users, and how it can contribute and be evaluated. It shows that URPs are structures that value the sharing of experiential knowledge of its members, humanise decision‐making and give meaning to the work done by scientific professionals. Patient or Public Contribution One patient–researcher has contributed to the preparation and writing of this manuscript.